AGB yields and Galactic Chemical Evolution: last updated. Issue 1 (January 2016) - Bisterzo, S; Travaglio, C; Wiescher, M; Gallino, R; Köppeler, F; Straniero, O; Cristallo, S; Imbriani, G; Görres, J; deBoer, R J
Abstract: We study the s -process abundances at the epoch of the Solar-system formation as the outcome of nucleosynthesis occurring in AGB stars of various masses and metallicities. The calculations have been performed with the Galactic chemical evolution (GCE) model presented by [1, 2]. With respect to previous works, we used updated solar meteoritic abundances, a neutron capture cross section network that includes the most recent measurements, and we implemented the s -process yields with an extended range of AGB initial masses. The new set of AGB yields includes a new evaluation of the 22 Ne(α, n) 25 Mg rate, which takes into account the most recent experimental information.